PENGANTAR METODOLOGI STUDI ISLAM - Andre Maulana Apriansyah; Adilatul Hijati; Qori Mumtahanah; Maftuh Ajmain (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the introduction to the methodology of Islamic studies as a scientific foundation for understanding Islamic teachings in a systematic, comprehensive, and contextual manner. The methodology of Islamic studies not only discusses ways of interpreting religious texts but also includes approaches, methods, and frameworks used to analyze Islam as both a doctrine and a social phenomenon. This research employs a library research method with a descriptive-analytical approach using relevant literature sources. The findings indicate that the methodology of Islamic studies plays an important role in integrating various approaches such as theological, historical, sociological, and philosophical perspectives. Thus, Islamic studies are not merely normative but are also capable of addressing contemporary social dynamics. Furthermore, a proper understanding of methodology helps prevent misinterpretations of Islamic teachings and encourages critical and scientific thinking. Therefore, mastering the methodology of Islamic studies is essential for the development of Islamic scholarship in the modern era.